El género Pleurosorus (Aspleniaceae) en la Península Ibérica. - Salvo-Tierra, Ángel Enrique (Universidad Complutense de Madrid, 1979)
In this study, a morphological, ecological, and chorological study of the genus Pleurosorus in the Iberian Peninsula was conducted. The validity of this species is discussed, and a new species is described: Pleurosorus nevadensis.
https://revistas.ucm.es/index.php/LAZA/acceso
Keywords: Aspleniáceas - Península Ibérica; Pteridophyte; Taxonomy; Pleurosorus